Comparative histological evaluations of the sublingual salivary glands of EBN swiftlets (Aerodramus fuciphagus) in man-made houses and natural caves - Ibrahim, Muhammad Marwan; Abu Bakar @ Zakaria, Md Zuki; Mat Amin, Fhaisol; Omar, Abdul Rahman (Universiti Putra Malaysia Press, 2017)
One of the most precious edible bird's nests (EBN) is constructed by the white-nest swiftlet (Aerodramus). However, different swiftlet populations might have different food intakes as a result of their different habitat sources. This situation will likely influence the secretion of the salivary gland. EBN is built from the saliva of the swiftlets. The major function of the salivary gland is to secrete saliva. This study was conducted with the aim of defining and comparing the histological structures of the sublingual salivary gland and its mucin content found in two separate populations of house-farm and cave white-nest swiftlets. Samples were collected from Seri Iskandar, Perak, Malaysia (04°20.824´N, 100°52.826´E) and Gomantong caves, Sabah, Malaysia (5°31.46.5´N, 118°4.29.6´E). It was found that the largest visible salivary gland present in both populations was the sublingual gland. The glands were stained with hematoxylin and eosin (H & E) stain and a combination of Alcian blue (AB) with periodic acid-Schiff (PAS) stain. The H&E stain displayed a broad range of cytoplasmic, nuclear and extracellular matrix features. The parenchyma of the cave swiftlet population appeared foamy due to high mucous secretion whereas the cells of the house-farm population could clearly be seen to be separated because of less mucous secretion. There was a clear difference in density and abundance of mucous acini cells in which the samples from the cave population were compacted with these cells. AB-PAS stains revealed full complement of tissue proteoglycans and acidic-mucin, neutral-mucin and mixtures of acidic and neutral mucins. The cave population exhibited higher concentrations of acidic, neutral, and mucins mixture compared with those from the house-farm. This is probably caused by several combinations of factors such as difference in dietary habit, habitat preference and age of the swiftlet.